Small EVs From Adipose‐Derived MSCs Modulate Epidermal Barrier and Inflammation Via Sphingosine‐1‐Phosphate Signaling Pathway - Kyong‐Oh Shin; Jun Ho Lee; Seungwoo Chae; Karin Goto; Hahyun An; Joan S. Wakefield; Dae Hyun Ha; Healim Lee; Kyojin Lee; Hyunju Lee; Ella Shin; Min Ji Kang; et al. (Journal of Extracellular Vesicles)
ABSTRACT Epidermal permeability barrier defects are associated with several skin diseases, including atopic dermatitis (AD). Using an AD mouse model, we previously demonstrated that topically administered small extracellular vesicles (sEVs) (prepared following the International Society of Extracellular Vesicles recommendations) from human adipose tissue‐derived mesenchymal stem cells (ASC) ameliorate skin inflammation and normalize barrier function in parallel with increased ceramide (a key barrier lipid) production. To elucidate how ASC‐sEVs alleviate these AD skin abnormalities, we characterized lipids and ceramide metabolic enzymes in ASC‐sEVs versus donor ASCs. Our study revealed that free fatty acid, ceramide, and sphingomyelin are enriched in ASC‐sEVs versus donor ASCs, while the synthetic enzymes of ceramide (and acidic sphingomyelinase), and sphingosine‐1‐phosphate (sphingosine kinase) are significantly higher in ASC‐sEVs versus donor ASCs. Conversely, ceramide (ceramidase), and sphingosine‐1‐phosphate hydrolytic enzymes (sphingosine‐1‐phosphate lyase and sphingosine‐1‐phosphate phosphatase) are lower in ASC‐sEVs, suggesting that ceramide and sphingosine‐1‐phosphate levels could elevate in cells that receive ASC‐sEVs. ASC‐sEV‐mediated increases in sphingosine‐1‐phosphate suppress pro‐inflammatory cytokine production in AD‐model human keratinocytes. Additionally, keratinocyte differentiation, which is required for a competent epidermal permeability barrier, was restored in AD‐model human keratinocytes treated with ASC‐sEVs. Taken together, cells that endocytose ASC‐sEVs can normalize epidermal permeability barrier function as well as alleviate inflammation by stimulating a sphingosine‐1‐phosphate signalling pathway.